Effects of Smoking on Dental Implant Procedures - M Ketabi; M Ketabi (Isfahan University of Medical Sciences, 2007)
Introduction: During using osseointegrated dental implants, as a foundation for the prosthetic replacement of missing teeth, failures and complications inevitably occur. The aim of this literature review was to present the studies related to the effects of smoking on dental implant procedures.Methods and Materials: Relevant clinical English studies published up to end of May 2008 through Medline and Cochrane Oral Health Group database (COHG) were surveyed. This was supplemented with a hand search of selected dental journals and text books at libraries of Isfahan School of Dentistry and School of Dentistry at the University of Toronto. Agreement between the reviewers was determined performing k-statistic. Disagreements were resolved by evaluation of the full texts and discussion. Due to heterogeneity of the factors in different studies, no meta-analysis performed. The results of different studies presented in a systematic manner.Conclusion: Implant complications, marginal bone loss and implant failure were higher in smokers than non-smokers. The deleterious effects of cigarette smoking are dose dependent and were more pronounced in upper jaw. The negative effects of smoking were also less observed in medium rough surfaced implants. The success rates of GBR and SFEA procedures with implants were much lower in smokers. Appropriate oral hygiene instructions should be given and the deleterious effects of smoking on implant therapy should be highlighted. In patients who do not quit smoking, antibiotic should be given before surgery. Patient must also instruct not to smoke 1 week before and 8 weeks after surgery. Key words: Implant, Smoking, Implant failure, Implant complications